(untitled) (Research, Society and Development, 2025)
Objective: To explore and synthesize the existing scientific evidence regarding the key motivators and barriers that impact university students’ decisions to donate blood. Introduction: Although blood donation is essential for public health, donation rates often do not meet the necessary demand. College students are a potential group for donation campaigns because they are young and healthy. Understanding the factors that influence this population to donate blood can contribute to more effective blood collection and retention strategies. Inclusion criteria: The research question that will guide the inclusion of studies was constructed by the PCC strategy, where P- population (students), C-concept (factors that influence blood donation) and C-context (higher education environments): “What are the barriers and motivations for donating blood among students in higher education settings?” Methods: An integrative literature review will be carried out according to the steps described by Souza, 2010. A search will be carried out in a database in the Virtual Health Library (VHL), in the Scientific Electronic Library Online (Scielo) and in PubMed as these are the databases which concentrate a higher degree of indexing of health periodicals. Two independent reviewers will select the studies by title and abstract using the blind on tool in the Rayyan software. The full texts of the included articles will be read and analyzed and data will be extracted using a specific form. Results: Results will be interpreted in light of the literature review and discussed in relation to existing theories on blood donation behavior and health communication.